Skrining Fitokimia dan Penentuan Kadar Flavonoid Daun Kelor (Moringa oleifera L.) Desa Dolok Sinumbah dan Raja Maligas Kecamatan Hutabayu Raja - Yulia Yulia; Muhammad Idris; Rahmadina Rahmadina (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2022)
The benefits of Moringa leaves (Moringa oleifera L.) are trusted by the village community in treating various diseases such as antidiabetic, antihypertensive, and anticancer. This study aims to examine secondary metabolites through phytochemical screening and determination of flavonoid levels in the ethanol extract of Moringa leaves (Moringa oleifera L.) Dolok Sinumbah and Raja Maligas villages. The method used in this research is a descriptive survey. The results of the qualitative test with phytochemical screening showed that the ethanol extract of Moringa leaves (Moringa oleifera L.) was positive for flavonoids, saponins, tannins, and steroids. The results of the quantitative test to determine the flavonoid content of the ethanol extract of Moringa leaves (Moringa oleifera L.) are different in the two villages, namely the flavonoid content of Dolok Sinumbah Sinumbah Village of 94.1842 mgQE/gr and Raja Maligas of 87.5157 mgQE/gr using UV spectrophotometry. –Vis.